The Influence of Financial Performance, Managerial Ownership, and Capital Structure on Stock Price - Deby Meiyustriza (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2023)
This research aims to determine the influence of return on assets, return on equity, managerial ownership, and capital structure on share prices both partially and simultaneously. The method used for sampling was purposive sampling with several predetermined criteria. The sample obtained was 27 companies with a total of 135 data and the population in this study were companies in the primary consumer goods sector, food and beverage sub-sector which were listed on the Indonesian Stock Exchange for the 2017-2021 period. The regression method in this research uses panel data regression. The research results show that simultaneously return on assets, return on equity, managerial ownership and capital structure have a significant effect on stock prices. Partially, the return on assets variable has a significant positive effect on stock prices. Meanwhile, return on equity, managerial ownership, and capital structure partially do not have a significant effect in a positive direction on share prices.